Biocontrol of Macrophomina root rot of mungbean - and G. ARJUNAN, T. RAGUCHANDER, R. SAMIAPPAN (Indian Phytopathology, 2002)
Dry root rot in mungbean caused by Macrophomina phaseolina was reduced by the application of biocontrol agent Trichoderma viride isolates multiplied in organic substrates, such as coir pith, groundnut shell and press mud as row application in acid soil condition. Among the organic substrates, groundnut shell medium supported the production of maximum number of chlamydospores, better native Rhizobium nodulation and higher yield. Sclerotia number and root rot incidence were greatly reduced in groundnut shell as compared to coir pith and press mud.